Acculturation in Exile: Ideological Constructs of Migration in Julie Dash’s Film Daughters of the Dust - Fodor, Mónika (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Controversies of the American Experience have provoked the imaginations of scholars both inside and outside the United States for more than two centuries. The intricacy of American democracy was already perceived by early witnesses to American ironies, among them J. Hector St. John de Crévecoeur, Alexis de Tocqueville and Max Weber. Their observations concluded that democracy is complex and often intangible. This may have been the result of intricate social processes of migration and its ideological constructs such as exile, acculturation, and assimilationthat not only gave birth to but continue to form and reform American society even in our own day. The terms are widely discussed and understood from entirely different aspects, however, the dynamic nature of the processes is a basis for consent. The present paper intends to show the complex relationship of these concepts as well as to interpret Julie Dashs film Daughters of the Dust from the perspective of migration and its ideological constructs.